Healthcare needs of older adults: in their own words. Issue 1 (2nd January 2019) - Hold, Judith; Rodriguez, Darlene Xiomara; Skott-Myhre, Hans; Janke, Alix
ABSTRACT: Community-based health and human services professionals can play an important role in bolstering wellness through offering education to elderly residents and healthcare providers on how to address the unique needs of this population. The purpose of this study was to examine the healthcare needs of the elderly living in two metropolitan counties in Georgia that have experienced an increase in the number of elderly residents. Utilizing qualitative data garnered through focus groups, two main themes were identified: the role of exercise as a means of personal power and feelings of powerlessness. Participants' narratives reflected opportunities and situations fostering good health through exerting their personal power to alter or improve individual health. On the other hand, negative pathways leading away from optimal health were realized when participants felt powerless to change their health status. For health and human services professionals working with the elderly, these findings should be considered as population, personal well-being, and power changes overtime.